2016
DOI: 10.1016/j.abb.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and diabetes

Abstract: Zn 2+ ions are essential for the normal processing and storage of insulin and altered pancreatic insulin content is associated with all forms of diabetes mellitus. Work of the past decade has identified variants in the human SLC30A8 gene, encoding the zinc transporter ZnT8 which is expressed highly selectively on the secretory granule of pancreatic islet β and α cells, as affecting the risk of Type 2 Diabetes. Here, we review the regulation and roles of Zn 2+ ions in islet cells, the mechanisms through which S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
109
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 95 publications
(148 reference statements)
1
109
0
1
Order By: Relevance
“…Any chemistry that oxidizes or modifies these sulfhydryls lowers the zinc buffering capacity and increases the availability of free zinc ions. Free zinc ion concentrations are higher in cells from diabetic cardiac cells/tissues (61), decrease under hypoxia in β-cells (62), and double when β-cells are exposed to higher glucose concentrations (63). When free zinc ion concentrations increase zinc can bind to macromolecules/proteins that otherwise would not interact with zinc and affect their functions.…”
Section: The Role Of Zinc In Redox Homeostasismentioning
confidence: 99%
“…Any chemistry that oxidizes or modifies these sulfhydryls lowers the zinc buffering capacity and increases the availability of free zinc ions. Free zinc ion concentrations are higher in cells from diabetic cardiac cells/tissues (61), decrease under hypoxia in β-cells (62), and double when β-cells are exposed to higher glucose concentrations (63). When free zinc ion concentrations increase zinc can bind to macromolecules/proteins that otherwise would not interact with zinc and affect their functions.…”
Section: The Role Of Zinc In Redox Homeostasismentioning
confidence: 99%
“…
Zinc (Zn) is negatively associated with the incidence of coronary heart diseases in patients with type 2 diabetes [1], and copper (Cu) may also play a pivotal role in the pathogenesis of diabetes [2]. We reported that the serum Zn/Cu ratio was positively associated with glycemic control in patients with type 2 diabetes [3].
…”
mentioning
confidence: 75%
“…Огляд літератури /Literature Review/ может модифицировать экспрессию SLC30A8 и способствовать развитию СД 2-го типа [95].…”
unclassified